Groundwater recharge in basement aquifers in subhumid drylands of sub-Saharan Africa - D. Mudimbu; W. Namaona; M. C. Sinda; B. Brauns; D. C. Gooddy; W. G. Darling; K. Banda; E. Phiri; P. C. Nalivata; F. Mtambanengwe; P. Mapfumo; A. M. MacDonald; et al. (Hydrogeology Journal, 2024)
Characterising groundwater recharge is fundamental for sustainable groundwater management. This study focuses on assessing recharge in drylands using four experimental plots under different land-use practices in crystalline basement aquifers in three southern African countries (Chitedze in Malawi, Kabeleka and Liempe in Zambia, and Domboshawa in Zimbabwe). Several methods, including water-table fluctuation (WTF), chloride mass balance (CMB), water stable isotopes (δ 18 O and δ 2 H) and dissolved gases, were used to quantify annual recharge rates, recharge sources and groundwater residence times. This informed the development of a conceptual model of groundwater recharge in unpumped basement aquifers. Using WTF, across all sites/years, the range of annual median recharge was found to be in the range of 2.8–14.1% rainfall. Recharge was observed for most years across all sites and was controlled by hydrogeological settings, rainfall totals and antecedent conditions, i.e. the groundwater level at the end of the preceding dry season. Based on groundwater level observations and water stable isotope analysis, for sites where there has been extensive use of conservation agriculture (in time and space), there is some evidence of earlier and greater recharge compared to conventional agriculture at paired sites. Additionally, there is evidence of high lateral connectivity in shallow, permeable layers and high local connectivity in the aquifers which facilitate discharge to surface drainage. This leads to a lower proportion of modern recharge at these unpumped sites (typically <10%) compared to other studies using comparable methods in pumped boreholes, which highlights the importance of groundwater capture due to pumping.